Drug Delivery: Extracellular Vesicle Production Loaded with Nanoparticles and Drugs in a Trade‐off between Loading, Yield and Purity: Towards a Personalized Drug Delivery System (Adv. Biosys. 5/2017). Issue 5 (May 2017) - Piffoux, Max; Silva, Amanda K. A.; Lugagne, Jean‐Baptiste; Hersen, Pascal; Wilhelm, Claire; Gazeau, Florence
Abstract : The human body possesses its own outperforming delivery device in extracellular vesicles that circulate in all body fluids and act as a farreaching intercellular communication pathway. Engineering extracellular vesicles with therapeutic and imaging agents opens up unprecedented perspectives with a new generation of personalized drug delivery systems. In article number1700044, Florence Gazeau, Amanda K. A. Silva, and co‐workers compare methods of production, engineering, and purification of extracellular vesicles that challenge the road towards clinical translation.